Design and synthesis of functionalized coumarins as potential anti-austerity agents that eliminates cancer cells' tolerance to nutrition starvation. Issue 14 (15th July 2019) - Awale, Suresh; Okada, Takahiro; Dibwe, Dya Fita; Maruyama, Takahiro; Takahara, Satoyuki; Okada, Takuya; Endo, Satoshi; Toyooka, Naoki
Graphical abstract: Abstract: Human pancreatic tumor cells have inherent ability to tolerate nutrition starvation which enables them to survive in the hypovascular tumor microenvironment. Discovery of agents that selectively inhibit the cancer cells' tolerance to nutrition starvation leading to cancer cell death is a new anti-austerity approach in anti-cancer drug discovery. A series of coumarins derivatives were synthesized and evaluated for their anti-austerity activity against PANC-1 human pancreatic cancer cell line. The compound 7-Hydroxy-2-oxo-2 H -chromene-3-carboxylic acid (3-phenylpropyl)amide (2c ) showed highly potent selective cytotoxicity against PANC-1 cells under nutrient-deprived conditions, with a PC50 value of 0.44 μM, without exhibiting toxicity in normal, nutrient-rich medium. Compound 2c caused dramatic alterations in PANC-1 cell morphology, leading to cell death. The compound 2c was found to inhibit PANC-1 cell migration and colony formation in a concentration-dependent manner. The compound 2c is a lead structure for the anti-austerity drug development against pancreatic cancer.